Análise operacional de métodos de desbaste mecanizado em plantios de Pinus taeda - Berude, Leandro Christo (2019)
Due to the high costs of harvesting wood, especially when carried out in stands subjected to thinning, it became necessary to develop new models of operation. Thus, the objective of this study was to perform a comparative operational analysis between two models of slabs in Pinus taeda L. stands in the central-southern region of the state of Paraná, generating information for planning, cost reduction and better utilization of forest resources. The first model tested was the 5th line, conventionally used in companies, which consists of the systematic removal of the central line allowing the entry of the machines inside the field and of two adjacent lines, in a selective way. The second model tested was the 7th line, with systematic removal of the central and selective line of trees in the three adjacent lines. A study of the times and movements of the harvester and forwarder machines was carried out in both thinning treatments, comparing the times of the operational cycles, determining the operational efficiency, productivity, operating and production costs and energy yield of machines. An analysis was also made of the quality of the operations in relation to the length of the logs, height of the strains and damage caused by the machines in the remaining trees. The results show that the roughing model performed in the 5th line had shorter operating cycles for both machines, with a mean harvester productivity of 17.82 m3 .he-1 and 14.36 m3 .he-1 and the forwarder of 24.21 m3 .he-1 and 20.42 m3 .he-1 for the 5th and 7th row treatments, respectively. The cost of production was 10.47 R$.m-3 in the thinning carried out in the 5th line and 12.64 R$ .m-3 in the 7th line. The treatments presented a similar distribution of damages in the remaining trees. The largest amount of damage was caused by the harvester, in contrast the larger damages were caused by the forwarder.